Using importance and performance analysis to direct emerging rural destination development - Johannes Johannes; Edward Edward (Faculty of Economics and Business Mulawarman University, 2022)
Stakeholders' role in developing new tourist destinations is significant, especially in emerging destinations where the villagers or community needs to be involved. Accordingly, the research purpose is to explain stakeholders' appropriateness attributes in terms of importance and performance. Therefore, we surveyed with various institutions eight tourist stakeholders with a sample size of 65 units. The analytical tool used IPA, which used a Cartesian diagram to show attributes position. The result showed that the area (I) improvement should focus on tourist information and communication, and area (II) should be maintained; natural, transportation, destination activity, village involvement, and village government role. Furthermore, area III is the low priority due to the high performance: accommodation and culinary. Finally, the ignore area (IV) is the activity package, tourism networking, transparencies program, finance support, and human resource competence. Hence the main problem of the stakeholder holder's perspective is the coordination program. The local government could consider stakeholder's flexibility practice to enhance the destination by addressing each attribute to different stakeholders to be their functions. They must update them with contextual and relevant things about rural destinations.